Dampak Variasi Torsi Alternator terhadap Kinerja Inverter dan Kualitas Daya - Fajar, Aidil; Harahap, Partaonan; Oktrialdi, Benny; Amirrudin, Arfis (Fakultas Teknik UMSU, 2025)
The alternator is a crucial component in electrical systems that functions to convert mechanical energy into electrical energy. The torque applied to the alternator shaft significantly affects its performance. This study investigates the impact of torque variations on the performance of an inverter that receives power supply from the alternator. An experimental method was employed to test the alternator-inverter system under varying loads. The measured data includes voltage and current at the inverter output, as well as different torque levels used to drive the inverter. The results indicate that low torque produces unstable DC voltage. In the tests, the alternator drive operated at a speed of 1057 RPM, an angular velocity of 110.5 rad/s, and a torque of 9.049 Nm, resulting in the inverter being unable to provide ideal AC output. Conversely, higher and stable torque allows the inverter to generate AC voltage with a constant frequency close to its nominal value. These findings emphasize that the alternator's torque directly influences the stability and efficiency of the inverter. The main conclusion of this research is that the quality of power produced by the inverter is significantly affected by the stability of the alternator's torque, with the alternator output power being 1000 Watts and an efficiency of 90% or 0.9. Therefore, torque control is a critical component in the design of power supply systems reliant on alternators.